AN OVERVIEW OF PSYCHOLOGICAL WELL-BEING AMONG INMATES SERVING AS KITCHEN WORKERS AT CLASS IIB BANGKALAN STATE DETENTION CENTER - Firmansyah, Fiqi Rheza; Kurniawan, Andi (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The psychological well-being of inmates serving as kitchen trustees needs to be considered as an effort to maintain their security, order, motivation, and work quality in their daily tasks. This will affect their self-acceptance, positive relationships with others, autonomy, environmental mastery, life purpose, and self-development, enabling them to maximize their assistance to officers in providing daily meals to inmates, whose numbers are disproportionate to the existing kitchen trustees. This study uses the psychological well-being theory to understand the psychological well-being of inmates working as kitchen trustees. The research employs a qualitative method with a descriptive approach, utilizing both primary and secondary data sources, which include interviews, observations, and document studies. We conducted data analysis through the processes of data collection, data reduction, data presentation, and conclusion drawing. The results of the study indicate the need for an evaluation of the motives and reasons inmates become kitchen trustees, the weakening of positive relationships with others, difficulties in performing daily activities, handling challenges and shortages as kitchen trustees, unclear life vision, and the underdevelopment of their potential. Keyword: Kitchen Trustees; Prisoner; Psychological Well-Being